PERAN FISIOTERAPI SEBAGAI PENDAMPINGAN ORANG TUA DALAM MELAKUKAN ACTIVE CYCLE BREATHING EXERCISE PADA ASMA DI PUSKESMAS KARTINI PEMATANGSIANTAR - Isa Harpika Br. Ginting; Noni Herawati; Sontoso Simanjuntak (Yayasan Nusantara Hasana Berdikari, 2024)
This community service research examines the role of physiotherapy in assisting parents in managing asthma through the implementation of the Active Cycle Breathing Technique (ACBT) at the Kartini Community Health Center in Pematangsiantar. This activity involves education on breathing techniques, live demonstrations, and intensive support for parents and children with asthma. ACBT, which consists of three main components: Breathing Control, Deep Breathing or Thoracic Expansion Exercises, and Huffing/Forced Expiratory Technique, is intended to mobilize lung secretions, improve ventilation, and optimize cough effectiveness in asthma patients. In addition to asthma management, this technique has previously been applied to other respiratory conditions such as pulmonary tuberculosis and bronchopneumonia, proving its effectiveness in addressing respiratory problems and improving patients' quality of life. The results of the activity indicate an increase in parents' understanding and skills in performing breathing techniques and a decrease in the frequency of asthma symptoms in children. This report comprehensively describes the background, objectives, implementation methods, results and analysis of the activity, and conclusions from the implementation of ACBT as a non-pharmacological intervention in asthma management.